Efficacy of obstructive sleep apnea treatment by antileukotriene receptor and surgery therapy in children with adenotonsillar hypertrophy: A descriptive and cohort study - Tran-Minh, Dien; Phi-Thi-Quynh, Anh; Nguyen-Dinh, Phuc; Duong-Quy, Sy (Frontiers in Neurology, 2022)
Background Prevalence of obstructive sleep apnea (OSA) in children with adenotonsillar hypertrophy is high and related to the occlusion of the upper airway. The main treatments of OSA in these children is adenotonsillectomy. However, this intervention is an invasive method with a various success rate. Thus, the indications of tonsillectomy remain debatable and non-invasive treatment is still a potential choice in these patients. Methods It was a cross-sectional and interventional study. This study included children aged from 2 to 12 years-old who were diagnosed with OSA by respiratory polygraphy and had tonsillar hypertrophy with/without adenoid hypertrophy. All main data including age, gender, height, weight, body mass index (BMI), clinical symptoms, and medical history were recorded for analysis. Physical examination and endoscopy were done to evaluate the size of tonsillar and adenoid hypertrophy by using Brodsky and Likert classifications, respectively. The severity of OSA was done by using the classification of AHI severity for children. Results There were 114 patients (2–12 years old) with a mean age of 5.5 ± 2.1 years included in the present study. The main reasons for consultations were snoring (96.7%), a pause of breathing (57.1%), an effort to breathe (36.8%), unrefreshing sleep (32%), doziness (28.2%), and hyperactivity (26.3%). There were 36% of subjects with tonsillar hypertrophy grade 1–2, 48.2% with grade 3, and 15.8% with grade 4 (Brodsky classification); among them, there were 46.5% of subjects with grades 1–2 of adenoid hypertrophy, 45.6% with grade 3, and 7.0% with grade 4 (Likert classification). The mean AHI was 12.6 ± 11.2 event/h. There was a significant correlation between the mean AHI and the level of tonsillar and adenoid hypertrophy severity (r = 0.7601 and r = 0.7903; p < 0.05 and p < 0.05, respectively). The improvement of clinical symptoms of study subjects was found in both groups treated with ALR (antileukotriene receptor) or ST (surgery therapy). The symptoms related to OSA at night including snoring, struggle to breathe, sleeping with the mouth open, and stopping breathing during sleep were significantly improved after treatment with ATR and with ST (p < 0.001 and p = 0.001, respectively). The mean AHI was significantly reduced in comparison with before treatment in study subjects treated with ALR (0.9 ± 1.0 vs. 3.9 ± 2.7 events/h; p = 0.001) or with ST (3.5 ± 1.4 vs. 23.4 ± 13.1 events/h; p < 0.001). Conclusion The treatment of OSA due to adeno-tonsillar hypertrophy with ALR for moderate OSA or surgery for severe OSA might reduce the symptoms related to OSA at night and during the day.